Activity of Vsr endonucleases encoded by Neisseria gonorrhoeae FA1090 is influenced by MutL and MutS proteins - Monika Adamczyk-Popławska; Katarzyna Bandyra; Agnieszka Kwiatek (BMC Microbiology, 2018)
Abstract Background The functioning of DNA repair systems is based on correct interactions between proteins involved in DNA repair. Very Short Patch (VSP) repair is a DNA repair system that corrects mismatches resulting from the deamination of 5-methylcytosine. The key enzyme in the VSP system is Vsr endonuclease, which can cleave mismatched DNA independently of accessory proteins. Until now, in vivo activity has only been shown for V.EcoKDcm - the only Vsr endonuclease in Escherichia coli. Additionally, the VSP system of E. coli is the only one for which interactions between proteins of the system have been demonstrated. Neisseria gonorrhoeae FA1090 is the first bacterium that we previously demonstrated to encode two active in vitro Vsr endonucleases: V.NgoAXIII and V.NgoAXIV. Results We elucidate the mutator phenotype of N. gonorrhoeae mutants with disrupted genes encoding V.NgoAXIII or V.NgoAXIV endonuclease. Furthermore, we investigate the interactions between gonococcal Vsr endonucleases and MutL and MutS proteins. The Vsr endonucleases physically interact with gonococcal MutL protein but not with MutS protein. In the presence of the MutL protein, the efficiency of DNA cleavage by both V.NgoAXIII and V.NgoAXIV endonucleases increases, resulting in a decrease in the amount of Vsr enzyme required to complete digestion of mismatched DNA. Both Vsr endonucleases are also stimulated in vitro by the MutL protein of E. coli. In turn, the gonococcal MutS protein hinders DNA cleavage by the Vsr endonucleases. However, this effect is overridden in the presence of MutL, and furthermore, the simultaneous presence of MutL and MutS causes an increase in the efficiency of DNA cleavage by the Vsr endonucleases compared to the reaction catalyzed by V.NgoAXIII or V.NgoAXIV alone. Conclusions For the first time, interactions between proteins of the DNA repair system encoded by N. gonorrhoeae that are responsible for the correction of mismatches resulting from the 5-methylcytosine deamination were identified. The increase in activity of Vsr endonucleases in the presence of MutL protein could allow for reduced synthesis of the Vsr endonucleases in cells, and the susceptibility of gonococcal Vsr endonucleases on MutL protein of E. coli implies a universal mechanism of Vsr stimulation by MutL protein.